A 14-day regimen of esomeprazole 20 mg/day for frequent heartburn: durability of effects, symptomatic rebound, and treatment satisfaction. Issue 6 (17th August 2016) - Peura, David; Le Moigne, Anne; Pollack, Charles; Nagy, Peter; Lind, Tore
ABSTRACT: Objectives : Esomeprazole 20 mg once daily has been shown to be effective for treating frequent heartburn over 14 days in subjects who are likely to self-treat with over-the-counter medications. These analyses were conducted to assess durability of effects and symptomatic rebound after cessation of treatment, treatment satisfaction, and rescue antacid use with esomeprazole 20 mg once daily for 14 days. Methods : Adults with frequent heartburn (≥ two days/week in the past four weeks) were randomly assigned to 14 days of double-blind treatment with esomeprazole 20 mg or placebo in two identical multicenter studies. All subjects entered a 1-week single-blind placebo follow-up period after treatment. The results of the primary efficacy endpoints were reported previously. The percentage of heartburn-free days during the 1-week follow-up, use of rescue antacids, and treatment satisfaction, measured with the Global Assessment Questions instrument, are described. Results : The percentage of heartburn-free days was maintained during the 1-week follow-up period; the proportion was 43% among esomeprazole subjects in these studies, suggesting no evidence of symptomatic rebound. Rescue antacid use generally decreased compared with the run-in period in the 14-day treatment and 1-week follow-up periods. Significantly more subjects taking esomeprazole were "very satisfied" or "satisfied" with treatment versus placebo (Study 1: 78% vs. 63%, respectively, P = 0.0038; Study 2: 81% vs. 60%, respectively, P = 0.0002). Conclusions : Subjects who are likely to self-treat their frequent heartburn with over-the-counter medications reported satisfaction with esomeprazole 20 mg. Esomeprazole's treatment effect was maintained for ≥ one week after treatment ended, with no sign of symptomatic rebound. These trials were registered at ClinicalTrials.gov: NCT01370525; NCT01370538.